Application of the Listening Team Learning Model Assisted by Timeline Infographic Media in Increasing Interest in Learning for Class - Mouliana, Mouliana; Diansyah, Arfan; M Gultom, Imelda (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This research aims to increase students' interest in learning in history subjects by implementing the Listening Team Learning Model assisted by Timeline Infographic Media at SMA Negeri 14 Medan. The research method uses a qualitative approach with data collection techniques through questionnaires and observation of student activities. The first cycle showed poor results with a percentage of 40%, but in the second cycle, there was a significant improvement with a percentage of 80%. The results show that the application of this learning model succeeded in increasing students' interest in learning in history subjects